The Importance of Economic Factors As The Cause of Divorce In The Tulungagung Religious Court - Surjanti Surjanti; Bambang Slamet Eko S (Journal Research of Social Science, Economics, and Management, 2023)
Relate to the number of cases handled by the Tulungagung Religious Court which is dominated by divorce cases. There are two types of divorce, namely talak divorce and contested divorce. Where in this divorce case the divorce case is dominated by the plaintiff being the woman (wife) and the man (husband) as the defendant. The research method used is a qualitative descriptive research method, by explaining and describing the problem through the facts obtained in field research at trials and mediation. The results of this study are to focus on the background or causes of divorce in the November 2022 case at the Tulungagung Religious Court. The causes that dominate this divorce case are constant quarrels and disputes, leaving one party, and economic factors.